BC Teachers’ Federation v British Columbia: The Supreme Court Takes a School Holiday - Tucker, Eric (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2018)
SummaryConstitutional labour rights in Canada now protect workers’ freedom to organize and bargain collectively and to strike. These associational freedoms are especially important for public sector workers, the most frequent targets of legislation limiting their freedoms. However, the Supreme Court of Canada judgments recognizing these rights and freedoms have also introduced important ambiguities about their foundation, scope and level of protection. This brief comment locates these ambiguities in the context of Canada’s political economy and industrial relations regime, which are beset by contradiction and conflict. It then explores the origins and development of the jurisprudential ambiguities in constitutional labour rights through a survey of recent Supreme Court of Canada’s labour rights judgments, including most recently British Columbia Teachers’ Federation and British Columbia (2016).